Biobased alkylphenols from lignins via a two-step pyrolysis – Hydrodeoxygenation approach. (April 2017) - de Wild, P.J.; Huijgen, W.J.J.; Kloekhorst, A.; Chowdari, R.K.; Heeres, H.J.
Highlights: Two-stage approach for thermochemical conversion of lignin into biobased aromatics. Successful pyrolysis of various technical lignins into a phenolic bio-oil. Catalytic hydrodeoxygenation of bio-oils into alkylphenolics and other aromatics. For comparison, direct HDO of Kraft lignin for depolymerisation and deoxygenation. Relatively high product concentrations in bio-oil after two-stage approach. Abstract: Five technical lignins (three organosolv, Kraft and soda lignin) were depolymerised to produce monomeric biobased aromatics, particularly alkylphenols, by a new two-stage thermochemical approach consisting of dedicated pyrolysis followed by catalytic hydrodeoxygenation (HDO) of the resulting pyrolysis oils. Pyrolysis yielded a mixture of guaiacols, catechols and, optionally, syringols in addition to alkylphenols. HDO with heterogeneous catalysts (Ru/C, CoMo/alumina, phosphided NiMO/C) effectively directed the product mixture towards alkylphenols by, among others, demethoxylation. Up to 15 wt% monomeric aromatics of which 11 wt% alkylphenols was obtained (on the lignin intake) with limited solid formation (<3 wt% on lignin oil intake). For comparison, solid Kraft lignin was also directly hydrotreated for simultaneous depolymerisation and deoxygenation resulting in two times more alkylphenols. However, the alkylphenols concentration in the product oil is higher for the two-stage approach. Future research should compare direct hydrotreatment and the two-stage approach in more detail by techno-economic assessments.